John Steinbeck and Henry Fonda - Unknown:::Creator::::::::::::
On the left, Henry Fonda and his wife Shirlee, talking to John and Elaine Steinbeck at the Holland Society dinner; Waldorf Astoria. Steinbeck wears Medal of Freedom around neck. The Society was honoring Fonda, who was of Nederlandse heritage. This has been noted as Steinbeck's last public appearance. See also number 0-643. Original in safe (color; copy and negative black and white)